Can Fish and Shellfish Species from the Black Sea Supply Health Beneficial Amounts of Bioactive Fatty Acids? - Albena Merdzhanova (MDPI AG, 2021)
Fatty acids (FA) are among the most important natural biologically active compounds. A healthy diet involves the intake of different fatty acids especially from omega-3 (n-3) series. Seafood provides a very good source of polyunsaturated fatty acids (PUFAs), but in Bulgaria there is limited information regarding the n-3 PUFA contents in traditionally consumed seafood by the population. The aims of this study were to determine lipid content, omega-3 polyunsaturated fatty acids (EPA and DHA), and the recommended daily intake of eleven fish species, three bivalves, rapana, and shrimp harvested in the Western part of Black Sea, Bulgaria. Total lipids were extracted according to the method of Blight and Dyer and fatty acid composition was analyzed by GC/MS. Fatty acid profile showed differences among species. PUFA were found in high content among total lipids, especially in shellfish (60.67–68.9% of total lipids) compared to fish species (19.27–34.86% of total lipids). EPA was found in higher amounts in rapana (0.16 g/100 g ww) and two of pelagic species (up to 0.29 g/100 g ww), whereas DHA prevailed in demersal and the most of pelagic fish (0.16–1.92 g/100 g ww) and bivalves (0.16–1.92 g/100 g ww). The health beneficial n3/n6 and PUFA/SFA ratios were found in all analyzed species. The lower values of the lipid nutritional quality indices (AI < 1, TI < 1) and higher for h/H index (0.8–1.78 for fish and 1.52 to 4.67 for bivalves and shrimp) confirm that the commonly consumed Black Sea fish and shellfish may provide health benefits for local populations. This study shows the seafood amounts that can provide the minimum recommended intake of omega-3 polyunsaturated fatty acids.